RODINGITIZATION OF IRANIAN BASIC ROCKS: A NEW INTERPRETATION (Journal of Sciences, Islamic Republic of Iran)
Mineral paragenesis of rodingitized basic rocks of Iranian ophiolites are presented and metasomatic reactions between Ca+2 bearing aqueous fluids issued during serpentinization of host ultramafic rock – with magmatic minerals of basic rocks leading to present paragenesis of rodingites are discussed. It is concluded that Ca+2 rich aqueous fluid in equilibrium with serpentinite has high Ca+2 chemical potential to react with magmatic minerals of basic dykes resulting in lowering the free energy of system, appearance of a new mineral paragenesis and total or partial conversion of basic dykes to rodingites. A feedback mechanism is proposed to account for inter-relationship of serpentinization and rodingitization.